2019
DOI: 10.5539/jas.v11n16p187
|View full text |Cite
|
Sign up to set email alerts
|

Decomposed Buriti Stem and Nitrogen Application Rates on the Growth of Eugenia dysenterica DC (Myrtaceae) Seedlings

Abstract: The effects of substrates formulated with different proportions of decomposed buriti stem (Mauritia flexuosa) and the application of nitrogen fertilizer rates in the production of cagaita (Eugenia dysenterica DC.) seedlings were investigated in this study. The treatments were arranged in a completely randomized design, in a 3 × 5 factorial: three substrates formulated from different proportions of decomposed buriti stem (0, 25 and 50%) with a clay loam soil (Oxisol), and five N fertilizer rates (0; 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 8 publications
1
0
0
Order By: Relevance
“…Native species have different nutritional requirements (Cruz et al, 2006). In this sense, some species respond to nitrogen fertilization (Fonseca et al, 2019), while others do not respond, as we found with the cagaita (Eugenia dysenterica), species used in the experiment. This was also verified in studies that evaluated the effect of nitrogen fertilization on other species, such as cagaita (Duboc and Guerrini, 2007).…”
Section: Resultssupporting
confidence: 51%
“…Native species have different nutritional requirements (Cruz et al, 2006). In this sense, some species respond to nitrogen fertilization (Fonseca et al, 2019), while others do not respond, as we found with the cagaita (Eugenia dysenterica), species used in the experiment. This was also verified in studies that evaluated the effect of nitrogen fertilization on other species, such as cagaita (Duboc and Guerrini, 2007).…”
Section: Resultssupporting
confidence: 51%